Pemanfaatan Dana Lembaga Keuangan Mikro Oleh Penduduk Miskin Di Kabupaten Sumba Timur - Karolina A. Rewa; Emilia Ch. Kiha (Universitas Kristen Wira Wacana Sumba, 2016)
Micro Finance Institutions (MFI/Lembaga Keuangan Mikro (LKM) is one of the financial institutions that can be used by poor people, who do not have access to formal financial sectors, to get loans. The loans is to meet financial needs and to improve the economic condition or sustain life. It is expected, through LKM, the poor can help themselves. In other words, they become productive people in their community, break the chain of poverty and not dependent on various poverty reduction programs initiated by the government.The research is conducted on a sample of poor people who are members of the cooperative (Koperasi) who are already used and spent the funds of LKM in Sub- district Kambera and Sub-district Waingapu, East Sumba regency. This research is presented in qualitative descriptive, so it can describe in detail about the using and spending of the funds of LKM by the poor in East Sumba regency.The results shows that the average of the poor being investigated using funds lent by LKM for consumption needs is 65,75 percent higher than for the needs of businesses which is 56.75 percent while 10.75 percent not remembered. While the level of difficulty of the poor to return the funds, by average, is 5.75 people, in which they have difficulty to pay the loans and 4.5 people say that is not difficult to return the loans from LKM.Keywords: Microfinance Institutions, cooperatives, poverty, poor population